An investigation into heat dissipation from a stationary commercial vehicle disc brake in parked conditions. - Stevens, Kevin (Cranfield University, 2013)
Detailed understanding of heat dissipation from a stationary disc brake is of considerable importance for vehicle safety. This is essential for both park braking on inclines and for preventing brake fluid boiling in hydraulic brakes. Despite the experience proving the significance of such conditions, there is very little published data dealing with this phenomenon, and even ECE Regulation 13 does not specify hot parking braking performance. The problem of heat dissipation from stationary brake may appear simplistic but it is actually more complex than from a rotating disc, due to the lack of symmetry through or a dominant mode of heat transfer as natural convection is the only driving force behind the airflow. All three heat transfer modes exist in a transient process, with complex heat transfer paths within and between brake components. This Thesis investigates the cooling performance of a Commercial Vehicle (CV) brake whilst in stationary conditions. The research is predominantly orientated towards the thermal aspects of Electric Parking Brake (EPB) application in CVs. Contraction of large brake components after hot parking may lead to vehicle rollaway on inclines, with tragic consequences. An extensive theoretical and experimental study was conducted. An analytical model of a disc brake in free air was developed, enabling good prediction of disc temperatures and average surface convective heat transfer coefficients (hcₒnv) over the entire cooling range. A comprehensive CFD modelling of the 3-dimensional flowfield around the disc brake was also conducted, as well as predicting the surface convection coefficient distribution. Shear Stress Turbulence model was found to be most suitable for such studies. FE models were created to predict temperatures in all components of the brake assembly. A special Thermal Rig was developed for experimental validations, which uses an induction heater for heating the disc brake, and numerous surface mounted and embedded thermocouples for measuring component temperatures, as well as ‘free standing’ for determining air temperatures in specific points. IR cameras provided further temperature field information. The results clearly show little influence of the conductive heat dissipation mode. The study also showed, for the experimental arrangement used, a constant value of surface emissivity (ɛ = 0.92). With well-defined conductive and radiative heat dissipation modes, the emphasis was placed on investigating convective heat dissipation from a stationary disc brake. It has been demonstrated that the anti-coning straight vane design of brake disc does not cool effectively in stationary conditions. Expected ‘chimney effects’ in disc vent channels do not materialise due to large scale recirculation regions preventing airflow from entering the channels, which drastically reduces the convective cooling. Complex thermal interactions between the large assembly components are explained, with typical cooling time being just over an hour for disc brake cooling from 400°C to 100°C. Extracted heat transfer coefficients were used for establishing a complex FE assembly model, which enables accurate prediction of temperatures of individual components over the entire cooling period. The developed approach is used for predicting temperature of the existing brake assembly but is equally suited for generating new designs with more favourable characteristics. In addition to being a powerful design tool for assisting in EPB design and validation process, the methodology developed offers wide applications, such as thermal optimisation of the caliper housing for the installation of continuous wear monitoring sensors, smart slack adjusters (for low friction drag brakes), etc. EPBs in passenger cars have been successfully used for over 10 years now. They use a relatively simple approach for ensuring safe parking from hot by over-clamping (applying approximately twice the required actuating force) and re-clamping (repeated application after the vehicle has been parked). Large CV actuating forces prevent the use of over-clamping as this could damage the disc, whilst re-clamping would need to be repeated several times over a much longer period of time, requiring the vehicle battery to power the electronic systems for a longer period of time without recharging. Neither approach is acceptable, requiring a more in- depth thermal study of the CV brake in stationary conditions, as investigated in this Thesis. In addition to technical, there are marketing and financial aspects which make EPB introduction and acceptance in commercial vehicles very different to passenger car applications. Such an investigation was conducted, exploring the market the CV EPB will be sold in and whether it would accept the new technology. Two questionnaire analyses were carried out, with the second giving the respondent detailed information about the EPB. It was found that using an informed, knowledge based approach yielded more positive feedback to the proposed product. The outcome may be even considered more contrary than expected, rather than instigating mistrust, the new CV EPB technology created interest. Furthermore, reports of pneumatic malfunction indicated that independence from the pneumatic system should be used as the key selling point for the EPB, for all beneficiary segments.
Keywords: Benefit analysis; questionnaire analysis; numerical modelling; CFD; FE; disc brake cooling; brake assembly